Bateson, as três aprendizagens e suas relações com os professores e sua profissão não-regulamentada - Kader, Cárla Callegaro Corrêa (Linguagens & Cidadania, 2017)
This paper aims to treat about the studies of Gregory Bateson in relation to the processes of communication, related to the Cybernetic and to the Systems Theory, focusing in the three sorts of learning and searching a relationship with teaching. The results, according to the bibliographic review, turned possible the reflections about the role of teaching, besides showing the fragility of a non-regulamented profession as the teacher.